Microcrystalline cellulose, polylactic acid and polypropylene biocomposites and its morphological, mechanical, thermal and rheological properties. (1st March 2020) - Mohan Bhasney, Siddharth; Kumar, Amit; Katiyar, Vimal
Abstract: Modification of mechanical, morphological, thermal and rheological properties of the polymers via melt blending method has been an area of great interest. The present work describes the fabrication of microcrystalline cellulose (MCC) fibre with polylactic acid (PLA) and polypropylene (PP) blend by twin screw extruder to optimize melt processability of the PLA matrix. Compared to PLA, the tensile strength and percentage elongation of PLA80/19.9PP/0.1MCC biocomposites were reduced by 32% and 4%, respectively. No significant improvement was achieved in the Tg and Tc of the MCC based biocomposites. The PLA spherulite growth rate in PLA80/19.5PP/0.5MCC biocomposite was enhanced to 2.91 μm/min compared to pure PLA matrix (2.53 μm/min). The storage modulus of PLA was increased from low to high frequency while complex viscosity of PLA and its biocomposites showed shear thinning behaviour at a frequency range of 0.1–100 rad/s. Both PLA and PP, showed hydrophobic characteristics. Incorporation of MCC fibres resulted in the decrease in water contact angles of the biocomposites to 62°. Thus, it can be concluded that blending of MCC fibres results in considerable changes in the properties of the PLA and PP polymers. Graphical abstract: Image 1